English Fun Reading (ELFI) as Learning Media on Reading Skill for Vocational High School - nisak nur, Luluk choirun; Mu'ammalatun, Astuti; Ma'arif, Iin Baroroh; Ni'mah, Fauziyatun (SCHOOLAR: Social and Literature Study in Education, 2024)
The purpose of this research is to design ELFI (English Fun Reading) based on an android for Reading lessons for X-grade students of vocational high school TI An-Najiyah Jombang. Then researcher make product in the application for learning media. This research used Research and Development method (R&D) that the researcher adapted from ADDIE (Analyze, Design, Development, Implementation, and Evaluation). Based on the data on the development phase, the researcher got 91% on media validation which was categorized as a â€œworthy categoryâ€ classification. While the result of material validation was 97% also categorized as a â€œworthy categoryâ€ classification. Moreover, on implement phase, the result of studentsâ€™ responses was 90% which could be categorized as an â€œinteresting categoryâ€ classification. From the data that this research showed, it can be said that this application was feasible and can be applied to Vocational High School Level.